Out of the woods: Driftwood insights into Holocene pan-Arctic sea ice dynamics - Hole, GM; Macias-Fauria, M (American Geophysical Union, 2017)
The collation of 913 driftwood samples from across the western Arctic, with spatiotemporal distribution and available provenance data, enabled the production of a high-resolution proxy-based reconstruction of Holocene Arctic Ocean surface current and sea ice dynamics. Regionally bounded, driftwood-based sea ice reconstructions studies suggest spatiotemporally complex past Arctic sea ice extent and movement; however, a large-scale compilation of Holocene Arctic driftwood has not previously been developed. Sparse driftwood in the early Holocene (≥8.2 cal ka B.P.) deglacial period was followed by increased driftwood deposition in the warmer mid-Holocene (8.2–4.2 cal ka B.P.); characterized by an enhanced Transpolar Drift (TPD) ∼7 cal ka B.P., leading to sea ice loss through the Fram Strait. Driftwood incursion peaks show spatial E-W progression from the Eurasian Archipelagos to Greenland and the Canadian Arctic Archipelago, suggesting a progressive shift in the orientation of the TPD on centennial-millennial time scales and intermediate phases in the Arctic Oscillation. Late Holocene cooling (≤4.2 cal ka B.P.) is indicated by increased influx of probably North American Picea via a strengthened Beaufort Gyre (BG) which enhanced sea ice recirculation, starting in the western Arctic and progressing eastward. In recent millennia ( < 2 cal ka B.P.), a more variable driftwood record alternates between BG and TPD dominance on centennial time scales. To further constrain a spatiotemporal reconstruction of variations in Holocene ocean current and sea ice dynamics, a more definitive determination of driftwood provenance is recommended to build upon the current framework, such as through radiogenic isotope tracing and aDNA analysis.